A highly reliable radiation tolerant 13T SRAM cell for deep space applications. (June 2022) - Yekula, Ravi Teja; Pandey, Monalisa; Islam, Aminul
Abstract: This paper proposes a highly reliable radiation-tolerant 13T (HRRT 13T) SRAM cell for deep-space applications. The proposed SRAM cell design can effectively tolerate radiation events. The design metrics of the proposed SRAM cell are compared with conventionally used SRAM cells like QUCCE 10T, QUCCE 12T and standard 6T SRAM cells. The proposed SRAM cell consumes 9.4% and 14% lesser hold power ( H PWR ) compared to QUCCE 10T and QUCCE 12T SRAM cells, respectively. The proposed SRAM cell exhibits 12.7%, 3.63% and 11.7% shorter read access time ( T RA ) compared to QUCCE 10T, QUCCE 12T and 6T SRAM cells, respectively at a nominal supply voltage ( V DD ) of 0.7 V. The proposed HRRT 13T SRAM cell exhibits higher read stability compared to other conventionally used SRAM cells. This has been validated by 2.92×, 2.33× and 2.06× higher read static noise margin (RSNM) exhibited by the proposed cell compared to the 6T, QUCCE 10T and QUCCE 12T SRAM cells, respectively at V DD  = 0.7 V. The proposed SRAM cell exhibits high radiation tolerance capability compared to the conventionally used SRAM cells. This has been proved by 94.1%, 17.8% and 10.0% higher critical charge ( Q C ) of the proposed cell compared to 6T, QUCCE 10T and QUCCE 12T SRAM cells, respectively at V DD  = 0.7 V. The proposed cell achieves all these improvements at the expense of 1.05×, 1.38× and 1.36× longer write delay ( T WA ) compared to QUCCE 10T, QUCCE 12T and 6T SRAM cells, respectively at V DD  = 0.7 V. Extensive simulations on SPICE using 16-nm CMOS technology are performed to validate the theoretical design of the proposed SRAM cell. Highlights: This paper proposes a highly reliable radiation-hardened 13T SRAM Cell. The proposed cell employs a differential read technique to provide a shorter read access time. It exhibits higher Read Static Noise Margin (RSNM), which makes it read upset tolerant. It achieves 17.8% improvement in Critical Charge, which proves its robustness against radiation hazard.